Controlling Domain Wall Pinning in Planar Nanowires by Selecting Domain Wall Type and its Application in a Memory Concept - Atkinson, D.; Eastwood, D.S.; Bogart, L.K. (Applied Physics Letters, 2008)
Here, we report on the control of domain wall pinning at notch features patterned in Permalloy planar nanowires by selecting the micromagnetic configuration of the domain wall using a transverse magnetic field. The domain wall behavior was investigated both experimentally using focused magneto-optic Kerr effect measurements of lithographically patterned nanowires and with micromagnetic simulations. The pinning behavior observed is utilized in a concept for multibit memory cells applicable as the free layer in magnetic random access memory where the domain structure is defined by the location of domain walls that either pin or passby pinning structures depending upon the domain wall configuration selected.
EPrint Processing Status: Full text deposited in DRO
Keywords: Kerr magneto-optical effect; Magnetic domain walls; Nanowires; Permalloy; Random-access storage.